Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s12262-010-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Centchroman Regresses Mastalgia: A Randomized Comparison with Danazol

Abstract: We conducted a randomized trial to evaluate effectiveness of Centchroman in control of mastalgia and compared it with Danazol. Research Question-Is proportion of pain relief achieved by Centchroman similar to or inferior to that achieved by Danazol? In a randomized controlled trial of Centchroman vs. Danazol in mastalgia, 81 patients with mastalgia were studied. Thirty-nine patients were randomized to Danazol arm and 42 in Centchroman arm. The treatment was given for 12 weeks, followed by observation for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 21 publications
4
39
3
Order By: Relevance
“…This led to a 20% dropout rate in some trials. 6,7,15 Danazol (100-400 mg) results in weight gain, acne, greasy hair and skin, headache, nausea, hirsutism, decrease in the size of the breast and voice change (due to an androgenic effect). These side-effects occur in about one-quarter of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to a 20% dropout rate in some trials. 6,7,15 Danazol (100-400 mg) results in weight gain, acne, greasy hair and skin, headache, nausea, hirsutism, decrease in the size of the breast and voice change (due to an androgenic effect). These side-effects occur in about one-quarter of patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a randomized trial including 81 women, it was found to be superior to danazol for the treatment of mastalgia. 7 We studied the efficacy of ormeloxifene in women with pain in breast associated with or without fibrocystic breast disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hence to improve compliance and effect, in latter part of study, it was given as 30 mg once a day to 23 patients. In a randomized trial of 81 patients (42 randomized to centchroman and 39 to danazol), combining both alternate and daily dosage, centchroman was found to have response of 89.7 % (response being defined as number of women achieving reduction of pain to less than or equal to 3 on VAS of 0 to 10) whereas cases receiving danazol achieved a response of 69.4 % at 12 weeks of therapy [28]. A greater proportion of women in centchroman group continue to enjoy pain-free life even after the drug was stopped, suggesting a longer carry over effect.…”
Section: Hormone Replacement Therapy and Breast Painmentioning
confidence: 99%
“…In our study, 8 patients had menstrual irregularities, which were reversed after stopping medication. Menstrual irregularities were also noticed by Tejwani et al (19) ,Ragswaroob et al (20) , Kumar S et al (23) and Dhar A et al (12) .…”
Section: Discussionmentioning
confidence: 62%
“…In our study, the response with centchroman was 87.5% which is comparable to response noticed by DharA et al (12) 12 at the end of 12 weeks. Tejwani PL et al (19) noticed 100% response in their study of comparison between danazol and centchroman. Whereas 66%response was observed by Udaya Kumar Rajswaroob et al (20) in their study of effectiveness of centchroman on regression of mastalgia and fibroadenosis.…”
Section: Discussionmentioning
confidence: 96%